Prospects for foreign direct investment and the strategies of transnational corporations, 2004-2007 (UN New YorkUS, 2004)
Assesses overall foreign direct investment prospects and presents future trends for individual economic regions. Analyzes policy developments and implications.
Keywords: FOREIGN INVESTMENT